The potential role of Osteopontin in the maintenance of commensal bacteria homeostasis in the intestine - Ito, Koyu; Nakajima, Akira; Fukushima, Yuji; Suzuki, Keiichiro; Sakamoto, Keiko; Hamazaki, Yoko; Ogasawara, Kouetsu; Minato, Nagahiro; Hattori, Masakazu (PloS one, 2017)
Osteopontin (Opn), a multifunctional extracellular matrix protein, is implicated in the pathogenesis of various inflammatory disorders. Under physiologic conditions, its expression is restricted to certain tissues including bone and kidney tubule. However, cellular activation during disease development induces Opn expression in various immune cells. In this study, using Opn-EGFP knock-in (KI) mice we found that CD8α+ T cells in the intestinal tissues, including Peyer's patch, lamina propria and epithelium, express Opn under steady state conditions. Therefore, we examined the role of Opn-expressing CD8α+ T cells in intestinal homeostasis. Interestingly, Opn knockout (KO) mice had altered fecal microflora concordant with a reduction of TCRγδ+ intraepithelial lymphocytes (IELs). Consistent with this result, both treatment with anti-Opn blocking antibody and deficiency of Opn resulted in decreased survival of TCRγδ+ and TCRαβ+ IELs. This data suggests that a possibility that Opn may function as a survival factor for IELs in the intestinal tissue. Collectively, these data suggest the possibility that Opn might regulate the homeostasis of intestinal microflora through maintenance of TCRγδ+ IELs, possibly by support of IEL survival.